Prolactin Response to a Submaximal Dose of Ghrelin in Different Phases of the Normal Menstrual Cycle - Christina I. Messini; George Anifandis; Panagiotis Georgoulias; Konstantinos Dafopoulos; George Sveronis; Alexandros Daponte; Ioannis E. Messinis (Medicina)
Background and Objectives: A similar secretory pattern of prolactin (PRL) and growth hormone (GH) during the menstrual cycle has been reported in response to a high dose of ghrelin in adult healthy women. The present study aimed to assess the pattern of PRL and GH secretions in response to a submaximal dose of ghrelin during different menstrual phases in adult healthy women. Materials and Methods: Eight female subjects with normal cyclicity were enrolled. These subjects were either in the early follicular (EF), late follicular (LF), or mid-luteal (ML) phase of their cycles. Each subject received an IV dose of normal saline (2 mL each time) during the first cycle after enrollment, followed by an IV dose of ghrelin (0.30 μg/kg bw) in the second cycle. The blood samples were collected before and after the IV dosage at −15, 0, 15, 30, 45, 60, 75, 90 and 120 min, where 0 min denotes the time of IV dosage. Results: All the enrolled subjects experienced ovulatory cycles as assessed by increased serum progesterone levels. Serum estradiol levels were significantly higher in the LF than in the EF (p < 0.001) and ML phases (p < 0.01); these levels were also significantly higher in the ML than in the EF phase (p < 0.01). The administration of saline did not affect serum GH or PRL levels. Following the administration of ghrelin, plasma ghrelin levels and serum GH levels increased significantly (p < 0.001). The response amplitude of GH was similar in the three stages of cycle 2. In contrast to GH, the ghrelin injection induced a significant increase in serum PRL levels only in the LF phase (p < 0.05). Conclusions: These results show, for the first time, a different pattern of PRL and GH in response to a submaximal dose of ghrelin during the normal menstrual cycle. It is suggested that the ghrelin threshold for pituitary lactotrophs is higher than for somatotrophs and that, unlike GH, ghrelin-stimulated PRL secretion can be influenced by ovarian steroids.